2012
DOI: 10.1524/ract.2012.1962
|View full text |Cite
|
Sign up to set email alerts
|

A review of the demonstration of innovative solvent extraction processes for the recovery of trivalent minor actinides from PUREX raffinate

Abstract: Summary. The selective partitioning (P) of long-lived minor actinides from highly active waste solutions and their transmutation (T) to short-lived or stable isotopes by nuclear reactions will reduce the long-term hazard of the high-level waste and significantly shorten the time needed to ensure their safe confinement in a repository. The present paper summarizes the on-going research activities at Forschungszentrum Jülich (FZJ), Karlsruher Institut für Technologie (KIT) and Institute for Transuranium Elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 48 publications
2
92
0
1
Order By: Relevance
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…The minor actinides are recovered from a PUREX raffinate by selective extraction. 3,4 The implications of this strategy are the subject of several studies. 5,6 These strategies at some point require separating trivalent actinides, An(III) = Am(III), Cm(III) from the chemically similar lanthanides, Ln(III), generated by nuclear fission.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The processes that have been developed over the past 20 years, are mainly based on the co-extraction of trivalent actinides and lanthanides and their subsequent separation [2,11]. The separation of An(III) + Ln(III) from PUREX raffi nate in a process called DIAMEX (diamide extraction) was proposed in the 1980s [12].…”
Section: Reprocessability Of Molybdenum and Magnesia Based Inert Matrmentioning
confidence: 99%
“…Plutonium and MA (especially americium) are of particular concern with respect to long-term radiotoxicity, heat load issues and proliferation risks. The partitioning and transmutation (P&T) of MA in accelerator driven systems (ADS) is one possibility to cope with this problem [1][2][3].…”
Section: Introductionmentioning
confidence: 99%